Excellence and Renewal: Digital Transformation Patterns in the Hungarian Business Services Sector - Móricz, Péter; Marciniak, Róbert; Baksa, Máté (Vezetéstudomány / Budapest Management Review, 2022)
In the past few years, there has been an explosion of scholarly interest in the field of digital transformation of companies. The extant literature mostly focuses on the manufacturing industry and fails to explain the causes and consequences of digital transformation in the business services sector. This paper examines what digitalization’s primary purposes are and how management and organizational practices stimulate the digital transformation of business service centers. Four research case studies were developed and presented based on eighteen interviews with company experts and managers. The authors concluded that excellence in existing capabilities and organizational renewal are both key drivers of digital transformation projects in business service centers. They argue that rigorous top-down strategy formulation and implementation is not the only way and the building of organizational capabilities such as effective idea generation, small-scale developments, upscaling, and bricolage can also lead to successful digital innovations in the business services sector.